Community Empowerment Through Selling Price Determination Training at The Border Market of Humusu C Village, Insana District, North Central Timor Regency - Odriana Veronica Moi, Maria; Wada Betu, Kristina; Yohanes William Timuneno, Antonius; Cecilia Pah, Viany; M.T Dawu, Leopold; Brito, Manuel; Canciao Freitas, Joao (CV. Inara, 2024)
This service will be carried out at the border market of Humusu C Village, Insana District, North Central Timor Regency, East Nusa Tenggara Province. The problems experienced by the village are composed in two types of problems, namely accounting problems, and financial management problems with the following details: Accounting problems faced by Humusu C Village include:lack of understanding in financial records so that they are unable to get out of poverty, inadequate knowledge of business concepts, so they are unable to set goals for economic activities carried out. Furthermore, the financial management problem faced by Humusu C Village is a lack of understanding in determining the price of goods sold, resulting in prices that are too low on the products sold and very minimal profits.1) Lack of understanding in financial records; 2) Knowledge of weak business concepts; 3) Inability to set targets and evaluate the business. Financial management problems faced by Humusu C Village include: 1) Putting prices too low and always reducing profits. Solutions offered to overcome these problems include socialization to communities directly involved in international transactions at the border market of Humusu C Village, Focus Group Discussion (FGD) with sellers in the Humusu C Village environment to ensure the determination of selling prices in the border market, and assistance of each team member with the seller group. With the solutions offered for the above problems, it is hoped that international transactions that occur in the border market of Humusu C Village can run according to the policies and rules set by the Government.